Artificial Intelligence Applications in Road Safety: Challenges and Opportunities in India - Shrawan Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Artificial Intelligence (AI) has emerged as a transformative technology in the domain of traffic safety, offering predictive, analytical, and adaptive solutions to complex mobility challenges. In the Indian context, where road accidents account for one of the highest global shares of fatalities, the integration of AI into transport planning and management is both urgent and promising. This paper critically explores the applications of AI in traffic safety within India, ranging from intelligent surveillance, accident prediction, automated enforcement, and real-time traffic management. Drawing upon secondary literature, government reports, and case studies, the study highlights opportunities and challenges in AI adoption, including infrastructural limitations, data availability, and ethical considerations. The findings suggest that while AI can significantly enhance traffic monitoring, enforcement, and road user behavior analysis, implementation barriers such as uneven digital infrastructure, financial constraints, and regulatory gaps must be addressed. The paper advocates for inclusive, context-sensitive, and technology-driven strategies that align AI integration with India’s broader transport and road safety goals. This alternative framing of the study emphasizes the dual nature of AI adoption in India’s road safety landscape. On one hand, AI technologies present unprecedented opportunities for improving traffic surveillance, predictive analytics, accident prevention, and real-time traffic management. On the other hand, their implementation in India is constrained by infrastructure gaps, fragmented data systems, regulatory challenges, and financial limitations. The title captures the essence of India’s road safety journey balancing the optimism of AI-driven innovation with the practical realities of resource and governance constraints. By focusing on both challenges and opportunities, the study highlights a pathway for policymakers, engineers, and researchers to strategically integrate AI into India’s road safety initiatives, ensuring sustainable and inclusive outcomes.